Analysis of Parkir Area Requirements at Universitas Internasional Batam - Apis Indica Adam; Yusra Aulia Sari (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2023)
The significant increase in the number of students at Batam International University. Along with the increase in good accreditation in all faculties, Batam Internasional University has become one of the campuses that is of interest to the community, especially the people of Batam city. This causes density to continue to increase, especially in campus parking areas. The method used is observation of research objects and secondary data collection from the campus. There are parking characteristics consisting of the number of vehicles on two-wheeled vehicles totaling 896 motorbikes, average duration = 0.25 hours, parking index = 62%, parking space requirement = 56 SRP, estimated land area = Â±1440 . With that, the land area required is 1344 and has reached the excisting area. In the charasteristics of class I car vehicles, it was found the number of incoming vehicles was 702, average duration = 0.18 hours, parking index = 18.84%, parking space requirement = 31 SRP, estimated land area = Â±3726 . With that, the land area required is 8073 and does not yet meet the available area.